Generalized fixed drug eruption suggesting potential association with dimenhydrinate: A rare case report - Suryaningsih, Betty Ekawati; Noegroho, Trijanto Agoeng (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Generalized fixed drug eruption (GFDE) is a specific variant of fixed drug eruption (FDE) characterized by multifocal lesions that recur upon exposure to a particular medication. This report describes a rare case of GFDE in a 54-year-old male, who presented with chief complaints of widespread erythema and pruritic, burning sensation. Physical examination revealed the patient to be in generally good condition dermatological status showed erosion on the hard palate, patches, erythematous macules, and partially ruptured bullae forming erosion in inguinal and genitals area, buttocks, thighs, lower legs, feet, axillae, hands, forearms, and back. The lesions were described as purplish round/oval erythematous patches, ranging from 1-4 cm in diameter, partially confluent, forming larger areas up to 6x7 cm, with bullae partially ruptured into erosion. The patient was admitted to the hospital, and treated with Ringer's lactate infusion, and an intravenous injection of 125 mg methylprednisolone. On the second day, the dose of intravenous methylprednisolone was reduced to 62.5 mg in the morning and the patient was administered a 10 mg cetirizine tablet orally in the evening, triamcinolone acetonide for oral lesions, a 15-minute NaCl 0.9% compress on the genitals twice a day, and desoximetasone 0.25% cream for all lesions. By the third day, the patient’s condition had improved, and he was then discharged. The prescribed home therapy regimen included a 16 mg methylprednisolone tablet in the morning, a 4 mg tablet in the afternoon, a 10 mg cetirizine tablet once daily, a 500 mg ciprofloxacin tablet twice daily, compress, and topical applications of triamcinolone acetonide for oral lesions and desoximetasone 0.25 % cream for all other lesions. A follow-up visit three days post-discharge indicated significant dermatological improvement. The diagnosis was established through anamnesis, physical examination, and appearance of skin disorder. Dimenhydrinate was identified as the potential causative agent.